2014
DOI: 10.1590/0103-6440201302398
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Silver Nanoparticles to Composite Resin: Effect on Physical and Bactericidal Properties In Vitro

Abstract: The objectives of this study were to evaluate physical properties and antibacterial activity of a light-activated composite modified with silver nanoparticles. Discs were produced with unmodified resin (control group -CG) and modified resin with silver nanoparticles at two concentrations, 0.3% wt (MR03) and 0.6% wt (MR06). Streptococcus mutans and Lactobacillus acidophilus biofilms were induced in vitro by incubation of discs in a 20% sucrose medium, followed by sonication and counting of viable cells after 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 19 publications
(33 reference statements)
0
40
0
1
Order By: Relevance
“…Surface roughness is one of the properties of tooth and restorative materials that influence the formation and accumulation of biofilm. On the rough and irregular surfaces the dental biofilm is formed in greater amounts and has quicker maturation when to flat surfaces (24). Past studies indicated that even a demineralized enamel surface, which presents a higher surface roughness than sound enamel, is able to retain a larger amount of biofilm when compared to the intact enamel (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…Surface roughness is one of the properties of tooth and restorative materials that influence the formation and accumulation of biofilm. On the rough and irregular surfaces the dental biofilm is formed in greater amounts and has quicker maturation when to flat surfaces (24). Past studies indicated that even a demineralized enamel surface, which presents a higher surface roughness than sound enamel, is able to retain a larger amount of biofilm when compared to the intact enamel (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of minimal surface roughness for the success of restorations has been well documented. [3][4][5]8,9 Despite the evolution of dental composites, surface defects on these materials persist.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the presence of irregularities on restoration surfaces can influence esthetics, allows for biofilm retention and discoloration, and contributes to secondary caries. 3 A high surface roughness can compromise the physical properties of composites and contributes to the wear of restorations. [4][5][6] In this context, the use of finishing and polishing techniques for composite resins is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that rough surfaces increase bone-to-implant contact. 32 However, rough surfaces are also more likely to facilitate biofilm formation in the oral cavity; 33 therefore, a significant increase in surface roughness is not desirable, especially for the trans-gingival parts of an implant. The aspect of surface wettability is regarded as the second most relevant factor in the dynamics of cell adhesion to the surface.…”
mentioning
confidence: 99%